Spatiotemporal and Vertical Distribution of Asian Tropopause Aerosol Layer Using Long-Term Multi-Source Data - Hongchao Liu; Ren Li; Junjie Ma (Remote Sensing, 2023)
The Asian tropopause aerosol layer (ATAL) is an enhanced aerosol concentration layer in the upper troposphere and lower stratosphere over Asia, and it has important effects on radiation balance, atmospheric circulation, regional climate, and atmospheric chemical processes. However, despite its importance, the specific structure and long-term variation trend of the ATAL have been rarely analyzed, which is critical for assessing the impact of ATAL on climate change and evaluating the performance of climate models. This study compared and analyzed the three-dimensional spatial distribution characteristics and temporal variability using CALIPSO, SAGEII, and MERRA-2 data and discussed the possible causes of the variation. The results showed that the ATAL began to appear in the mid-to-late 1990s and then strengthened rapidly until 2010, after which this trend was no longer observed. Moreover, significant heterogeneity existed in the distribution of aerosol concentration in the ATAL, showing north–south differences (NSDs) in both time and space. In addition, it was found that besides surface emissions, atmospheric circulation, the strength of convective transport, and stratosphere–troposphere exchange processes also contribute to this pattern. This study has important implications for quantifying the climate consequences of the ATAL.